Caracterização morfológica e funcional das células endoteliais de coelho e humanas cultivadas sobre superfícies metálicas tratadas a plasma - Braz, Janine Karla França da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Stents are metal structures used in cardiovascular ischemia. They are generally used in combination with antiplatelet drugs to prevent thrombus formation. However, the efficacy of endothelialization on the surface is reduced and increases the risk of restenosis in patients. Therefore, there is a search for treatments that modify the chemical and physical properties of metal surfaces to improve cell-material integration without the use of antiplatelet drugs. Plasma treatment makes nanometric modifications and improves cell adhesion, proliferation, and differentiation in metals, such as titanium and stainless steel. Titanium is an inert, corrosion-resistant metal, widely applied in the production of implants and commonly used in the form of alloys with nickel in the manufacture of stents. However 316L stainless steel is widely used in the biomedical area because it has good mechanical resistance; however, wear and tear can promote toxic effects on the patient. Metal stents are commonly tested in the in vivo model of the rabbit iliac artery, however, the use of rabbit endothelial cells for in vitro testing of metal surfaces is tasteless. In vitro tests may aid in understanding the mechanisms of interaction and integration between cells and the metal surface. In spite of this, there is no information about this aspect, as well as about the mechanical properties of the cells provoked by metals, and of the possible implications resulting from this interaction. Considering that the use of in vitro models is useful in understanding the mechanisms of interaction between cells and adhesion surfaces, this work evaluated the effect of metal surface modification on human and animal endothelial cells. For this, surfaces of nitrided and oxidized titanium and nitrided stainless steel with nanoscale roughness were produced. Then, these were characterized as wettability by the sessile gout method, roughness by atomic force microscopy and chemical composition by X-ray diffraction. Endothelial cells cultured on the surfaces were evaluated for morphology, adhesion, and viability. As well as the influence on the modification of the mechanical properties of the living endothelial cells on the plasma treated titanium surfaces by atomic force microscopy (AFM). Based on the methods used it is possible to affirm that the surface modifications promoted an improvement in the cell-surface integration. The rabbit endothelial cells obtained better results on the nitrided surface of the stainless steel when compared to the nitrided titanium. Human and rabbit cells behaved similarly for cell adhesion and viability on the surface of plasma oxidized titanium. The elastic properties are influenced by the plasma treated surface and this may aid in the applicability of the biomaterial in order to use it as an innovative therapy as a tool to evaluate the biocompatibility of the biomaterials with future use in metallic stents
Keywords: Biomaterial; cardiovascular; plasma; stent; viscoelasticidade; Biomaterial; cardiovascular; plasma; plasma; viscoelasticity; CIENCIAS AGRARIAS::MEDICINA VETERINARIA